2008
DOI: 10.1530/eje-07-0592
|View full text |Cite
|
Sign up to set email alerts
|

Free triiodothyronine plasma concentrations are positively associated with insulin secretion in euthyroid individuals

Abstract: Background: Thyroid hormones (TH) may influence glucose metabolism. Hyperthyroid subjects have higher insulin secretion rates when compared with euthyroid individuals. Objective: To evaluate the association between TH concentrations and insulin secretion in euthyroid, healthy Pima Indian adults (nZ55, 29G7 years, females/males 36/19) with normal glucose tolerance (NGT) admitted to a Clinical Research Unit. Methods: TSH, free thyroxine (FT 4 ), 3,5,30 -L-tri-iodothyronine (FT 3 ), and fasting plasma insulin (FP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
59
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 43 publications
1
59
0
2
Order By: Relevance
“…Unlike TSH, data regarding the circulating levels of free thyroid hormones are discrepant between different studies, which reported either increased or decreased serum concentrations of FT 3 (11,12,14), with normal or decreased FT 4 /FT 3 ratios (12,14). Discrepancy is most likely due to the inclusion of patients with different degrees of obesity, as assessed by BMI, or different fasting plasma insulin concentrations, which were recently demonstrated to be positively related to FT 3 levels, independently from plasma glucose concentration (20).…”
Section: Discussionmentioning
confidence: 94%
“…Unlike TSH, data regarding the circulating levels of free thyroid hormones are discrepant between different studies, which reported either increased or decreased serum concentrations of FT 3 (11,12,14), with normal or decreased FT 4 /FT 3 ratios (12,14). Discrepancy is most likely due to the inclusion of patients with different degrees of obesity, as assessed by BMI, or different fasting plasma insulin concentrations, which were recently demonstrated to be positively related to FT 3 levels, independently from plasma glucose concentration (20).…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, Bilgin and Pirgon (32) reported that obese adolescents with steatohepatitis had elevated values for fT3/fT4 ratio. Ortega et al (33) suggested that fT3 was related with insulin secretion in euthyroid subjects, and T3 levels may be involved in the regulation of insulin secretion. In another study, it was proposed that alterations in thyroid hormones could be the result rather than the source of the increasing weight (34).…”
Section: Discussionmentioning
confidence: 99%
“…In some recent studies, thyroid dysfunction (23) and even TSH within the normal range (19,24,25) were reported to be associated with insulin resistance and components of metabolic syndrome. By contrast, some other studies failed to detect a significant association between TSH and insulin resistance (19,21,22,26). It is difficult to prove a casual relationship between insulin resistance and thyroid hormones as both are influenced by weight status.…”
Section: Discussionmentioning
confidence: 91%
“…The relationship between hypothyroidism, obesity and insulin resistance is of clinical interest (19)(20)(21)(22). To elucidate the link between thyroid disorders and adipose tissue, various adipocytokines were previously studied (9-11), in which the most promising one was leptin.…”
Section: Discussionmentioning
confidence: 99%